Exploring African Logic: The Interplay of Ubuntu, Ezumezu and Dialetheia - Qusthan A. H. Firdaus (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2026)
The African philosophical concept of Ubuntu, which posits that a person’s identity is fundamentally constituted through their relationship with others, directly challenges the foundational assumptions of classical Aristotelian logic. This article re-evaluates Ubuntu, moving beyond its traditional philosophical interpretations to examine its compatibility with Ezumezu logic—an African logical system—and with modern formal logic. I argue that the relational identity at the heart of Ubuntu offers a compelling alternative to the core tenets of Aristotelian logic, in particular the principles of identity (A=A), non-contradiction (A and non-A cannot both be true), and the excluded middle (no middle value between A and non-A). By employing formal notation, the analysis provides a precise and unambiguous demonstration of the ways in which Ubuntu’s inherent relationality undermines these principles. Ultimately, the article shows that Ubuntu finds a more fitting and expressive framework in Ezumezu logic. Moreover, it offers robust philosophical support for modern dialetheism, the view that some contradictions can be true, thereby broadening our understanding of African philosophy and of the nature of truth itself.